Ihsanoglu, Ahmad Dawud. “A Comparative Analysis of the Islamic and Western Epistemological Models,” Year 6, Issue 22 (Fall 1421 AH/ 2000 CE), Pp. 11-34. - أوغلو, أحمد داود (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2000)
Ahmad Dawud Ihsanoglu’s article addresses the Western epistemological model, explaining the idea of epistemological definition of truth, the secularization of knowledge, the impact of Christian philosophy in the formulation of the mind during the Middle Ages, and how the post-Renaissance transformed into the “humanization of knowledge” on the basis of the experimental and material methods, citing the views of Hume, Locke, Kant, Spinoza, Hegel, Bradley, Els, and Popper. It then discusses Islamic knowledge in terms of the epistemological unity of truth, citing al-Baghdādī, Ibn Rushd, Ibn Ṭufayl, and Ibn Ḥazm. Lastly, it addresses the epistemological theory in the thought of modernists, citing the views of Marx, Husserl, Schiller, and Comte, and concluding with the current attempts to Islamize knowledge as a challenge to secular thought.